EMOTIONAL REGULATION IN YOUNG CHILDREN AT PEMBINA STATE KINDERGARTEN: THE KEY TO MENTAL HEALTH - Lu-lu Tsamrotul Fuadah; Sianturi, Risbon (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2025)
The capacity to manage emotions is a critical skill that should be cultivated from an early age, as it has a direct impact on both the mental and physical well-being of children. This research investigates the developmental process of emotional regulation in early childhood and its association with children’s health status. Conducted at TK Negeri Pembina, the study employed a qualitative descriptive approach, with data gathered through observations and interviews involving teachers and parents. The subjects in this research were 15 children in group B aged 5-6 years old with specifically 7 boys and 8 girls. To obtain comprehensive insights, the principal was interviewed to explore the school’s policies and instructional strategies aimed at fostering emotional regulation. Data collection employed three complementary methods, which are non-participant observation, semi-structured interviews, document analysis. Data analyzed by thematic analysis. The results indicate that a supportive environment, active teacher engagement, and effective parenting practices significantly enhance children’s emotional regulation abilities.